Brief counseling skills training for elementary school teachers in Barito Kuala Regency - Rudi Haryadi; Ainun Heiriyah; Irfan Fitriadi Z (Universitas Muhammadiyah Magelang, 2022)
The implementation of guidance and counseling in elementary and high schools as one of the integrated class teacher responsibilities has been clearly regulated by Permendikbud Number 111 of 2014. This training was provided as program support to increase the capability of teachers to carry out counseling assignments. A total of 39 elementary teachers participated in the 7 sessions, which included policy outreach activities, material delivery, simulations, and supervised practice. The training's results show that elementary school teachers in the Barito Kuala District's counseling skills generally improved from the low category (3.77) to the medium category (6.62). Based on the result, the elementary educators in the Barito Kuala district need to applied the new skills in practical settings in order to improve their counseling competencies.